Mixed post-consumer recycled polyolefins as a property tuning material for virgin polypropylene. (1st December 2019) - Curtzwiler, Greg W.; Schweitzer, Matthew; Li, Yifan; Jiang, Shan; Vorst, Keith L.
Abstract: Polyethylene and polypropylene are widely used packaging materials that are commonly present in the same waste-streams (e.g., beverage bottle enclosures, laminated flexible packaging). Since these immiscible plastics are difficult to separate with current recycling practices, it is critical to understand the influence of mixed polyolefin post-consumer recycled feedstock composition on key performance properties of recycled blends for widespread industrial adoption. This research comprehensively characterized the optical, thermal, mechanical, morphological, and gas barrier properties of melt blended virgin polypropylene/mixed post-consumer recycled polyolefin materials at different blend ratios. The results strongly indicate that polyolefin beverage container enclosures can be melt blended with virgin polypropylene to tune physical performance properties (74% increased yield stress, 49% increased strain at yield, 160% increased UV blocking, 30–40% gas transmission reduction) and simultaneously reduce environmental contamination. Most measured properties followed the Law of Mixtures which enables highly predictable and tunable properties via precision melt blending of post-consumer recycled and virgin plastic. We hypothesize that increased compatibilization of polyolefin amorphous regions from plastic oxidation and structural changes in the plastic crystalline domains directly influence plastic physical properties. These data fill current knowledge gaps that post-consumer materials can provide value beyond sustainability to justify innovative landfill diversion strategies and realize a more circular economy. Graphical abstract: Image 1 Highlights: Mixed post-consumer polyolefin can be used as a performance tuning material. Mechanical properties increased with addition of mixed post-consumer polyolefin. Gas barrier properties increased with mixed post-consumer polyolefin. Melt processing parameters did not require modification for blends containing post-consumer polyolefin.